Identification of phase-specific antigenic fractions of Coxiella burnetti by enzyme-linked immunosorbent assay. - Williams, J C (1986)
Antigenic fractions of Coxiella burnetii phase variants were identified with an enzyme-linked immunosorbent assay (ELISA). Immune sera from guinea pigs immunized with Formalin-inactivated phase I or phase II whole cells were used to measure the antigenic activity of whole cells and various soluble and particulate preparations. Phase-specific antigens of C. burnetii whole cells and fractions were compared by dose-response curves at different (antigen and antibody) dilutions. Water-soluble extracts prepared by meta-periodate, ether, and phenol extraction of phase I whole cells yielded antigenic fractions which reacted with anti-phase I antibodies. The extraction of phase I whole cells with dimethyl sulfoxide, trichloracetic acid, and Formalin yielded antigenic fractions which detected antibodies in both anti-phase I and -phase II sera. Interestingly, the trichloracetic acid extract of phase I whole cells also contained a component which bound nonimmune immunoglobulin. The sera of animals immunized with whole cells of the phase II Australian QD strain reacted with lipopolysaccharides of the phase I and phase II Nine Mile strains. Therefore, variations in lipopolysaccharide structure among phase variants of C. burnetii were detected as cross-reactions with immune sera from an interspecific strain. Comparisons of immunofluorescence, microagglutination, and the complement fixation assays with the ELISA indicated greater sensitivity and specificity of the ELISA for the measurement of phase-specific antigens and antibodies.